Pengembangan Media Pembelajaran Berbantuan Canva pada Materi Alat Perlindungan Diri di SMK Negeri 2 Gunungsitoli: Penelitian - Zebua, Persatuan; Harefa, Envilwan Berkat; Telaumbanua, Arisman; Telaumbanua, Aprianus (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to develop Canva-assisted learning media for the Occupational Health and Safety (OHS) subject at SMK Negeri 2 Gunungsitoli and to examine its validity, practicality, and effectiveness. The background of this research is the limited variety of instructional media used by teachers, which mainly rely on textbooks or simple presentations, resulting in low student motivation and difficulties in understanding both the concepts and practical application of OHS. The research employed a Research and Development (R&D) method with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). Research instruments included validation sheets, student response questionnaires, and learning outcome tests. The results showed that the media was categorized as “very valid,” achieved a practicality score of 96.48% (very practical), and reached an effectiveness level of 84.09% with all students surpassing the minimum passing grade. Thus, Canva-assisted media is proven valid, practical, and effective, and is suitable as an innovative alternative in digital-based vocational learning.